EFFECT OF LOW-DOSE NIACIN ON DYSLIPIDEMIA, SERUM PHOSPHORUS LEVELS AND ADVERSE EFFECTS IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Won Suk An; Hyo Jin Kang; Ki Hyun Kim (The Korean Society of Nephrology, 2012)
Niacin supplementation improves dyslipidemia and lowers serum phosphorus levels in chronic kidney disease (CKD) patients. However, its adverse effects, including hot flusing, hinder the administration of niacin. We evaluated whether low-dose niacin supplementation can improve dyslipidemia, lower serum phosphorus levels, and be administered with a low frequency of adverse effects in patients with CKD. We retrospectively analyzed the clinical records of CKD patients who had taken niacin from January, 2009 to June, 2011. We excluded patients with CKD1 and CKD 5. We then enrolled 31 CKD patients who had taken niacin at a fixed-dose of 500mg/day for 6 months. We also randomly selected 30 CKD patients who had been taking statin for 9 months as a control group. Among 34 CKD patients prescribed niacin, 5 patients (14%) complained of adverse effects, and 3 CKD patients (8%) discontinued niacin. There were no significant differences in baseline data between the niacin group and the control group. The proportion of patients in the niacin group who had been taking a statin, or omega-3 fatty acids was 67.7% and 48.8%, respectively. In the niacin group, high density lipoprotein cholesterol (HDL) levels was significantly increased (p<0.05), and triglyceride (p<0.05) at 12 weeks and 24 weeks compared to baseline levels. In the niacin group, phosphorous levels (p<0.05) were significantly decreased, and glomerular filtration rate (GFR) was significantly increased (p=0.016) at 24 weeks compared to baseline values; however, serum creatinine levels did not significantly change. Low dose niacin (500mg/day) had a low freqeuncy of adverse effects and also improved dyslipidemia, lowered serum phosphorus levels, and increased GFR in CKD patients. Further studies are needed to evaluate the long term effects of low-dose niacin for renal progression of CKD.